Musculoskeletal disorders related to dental hygienist profession. Issue 3 (9th June 2022) - Saccucci, Matteo; Zumbo, Giulia; Mercuri, Paola; Pranno, Nicola; Sotero, Selene; Zara, Francesca; Vozza, Iole
Abstract: Objectives: Musculoskeletal disorders (MSDs) are occupational illnesses concerned with different classes of professionals; dental hygienists are among those. The aim of this trial is to evaluate MSDs prevalence and significance of the symptoms in a sample of dental hygienists. Materials and Methods: A 20‐question questionnaire was administered to a sample of dental hygienists, via social networks. The variables taken into consideration were personal data, hours of sport, working habits, years of professional activity, working hours and number of patients per week, presence or absence of pain. Statistical Analysis: Data were evaluated using standard statistical analysis software, and an Excel database was created. Descriptive statistics were calculated for each variable. Group comparison was assessed by the chi‐square test of homogeneity and Fisher's exact test. ( p ‐value <0.05 as significant). Results: 468 questionnaires were examined: 396 females (85%) and 72 males (15%). The prevailing age was between 25 and 35. Among them, 91% referred to be suffering or have suffered MSDs. The most relevant affected muscular areas are neck (30.6%), shoulder (25.0%) and lumbosacral region (23.3%); the remaining 21.1% is divided among the other regions. Association and statistical analysis among the different variables showed how presence of MSDs negatively influences absenteeism and work performance; further research regarding ergonomics, type of seat, stretching and workout prevention would be important to strengthen the results collected. Conclusions: Musculoskeletal disorders diffusion among dental hygienists is particularly high due to lack of information; the majority of interviewees showed very little awareness of it; this led to a lack of effort in facing or possibly preventing these pathologies.